Identifikasi Pola Dan Fungsi Ruang Puri Agung Jro Kuta, Kecamatan Denpasar Utara, Provinsi Bali - Putra, Anak Agung Ngurah Reza Mahafira; Sugianthara, Anak Agung Gede; Astiningsih, Anak Agung Made (Jurnal Arsitektur Lansekap; Vol.9, No.2, Oktober 2023, 2023)
Identification Of Space Pattern and Function of Puri Agung Jro Kuta, North Denpasar Subistrict, Bali Province . Puri is a collection of building units with all their completeness which is the center of royal government in Bali. Puri has a different pattern of space with the pattern of space in traditional Balinese houses in general, but not all puris have the same pattern of space. One of the puris in Bali is Puri Jro Kuta. Puri Jro Kuta has its own uniqueness in terms of space patterns and some of its buildings. The environment around Puri Jro Kuta at first also followed the pattern of Balinese architectural villages in general, but as the times developed, there were some changes in the environment around puri. This research aims to identify the patterns and functions of space, buildings and building functions, as well as patterns and functions of Catus Patha Puri Jro Kuta. The research method uses a survey method with data collection techniques of observation, interviews, and literature study. The identification results of this study indicate that the spatial pattern of Puri Jro Kuta is divided into nine rooms based on the Sanga Mandala principle and there are several additional spaces. Each room has a different function supported by the existence of buildings that also have their respective functions. The spatial pattern of Catus Patha Puri Jro Kuta has changed over time, while the function of catus patha puri has not changed. The results of the research are expected to become a cultural information center which is a form of cultural preservation, so as to maintain the existence and sustainability of puri.